THU0374 Health Beliefs, Experiences and Educational Needs of Patients with Osteoporosis : A Qualitative Study by the Working Group Solid'os. (23rd January 2014) - Beauvais, C.; Lespessailles, E.; Magar, Y.; Thevenot, C.; Euller Ziegler, L.; Filaire, E.; Gendarme, S.; Legrand, K.; Lévy-Weil, F.; Aubraye, D.; Cortet, B.; Poivret, D.; et al.
Abstract : Background: Real life experience and health beliefs impact quality of life and adherence to medication. Educational management programs have proved beneficial for patients with osteoporosis (OP). Objectives: To understand perceptions and educational needs of patients with different types of osteoporosis. The aim was to target patients perceptive to help the construction of educational programs. Methods: Focus group were conducted with a semi directive interview guide developed by the multidisciplinary working group SOLID'OS including rheumatologists, health care professionals, members of a patient association and experts in qualitative research. Interviews involved 18 post-menopausal women with osteoporotic fractures (2 groups), 10 post-menopausal women without osteoporotic fractures (2 groups), 14 men with osteoporosis (2 groups) and 10 patients with corticosteroid (CS) -induced osteoporosis (2 groups). Each group included 4 to 10 patients in 7 different cities. Thematic analysis was performed. Results: A wide range of health beliefs about OP was found : OP is considered as a natural consequence of aging or on the contrary leads to dramatic feelings and self-depreciation. Patients regret the delay to diagnosis before fractures occur. Patients are in fear of new fractures and consequently limit their daily life activities. Patients with CS-induced osteoporosis take better care of the causal disease than of OP. Men have negative perceptions, considering that OP principally affects women. Men have difficulties to cope with the loss of their functional abilities. Patients have a rather good knowledge of treatment except for CS treated patients whose knowledge is lower. Some patients are confident in health care providers and medication efficacy whereas others focus on adverse effects and doubt of the benefit of treatments. All patients need support and look for evidence of treatments efficacy. Patients show a great interest for non-pharmacologic management such as calcium intake and physical activity. Errors are frequent about adverse effects of calcium and milk, which for instance is believed to cause arthritis. Patients feel that group follow up by health professionals will enhance their motivation especially for exercises. They show preferences for group education close to their place of residence. Men often go on the Internet for brief information and like booklets. Education should include physical activity, fall prevention and dietetics. The benefit of including partners remains doubtful for almost all patients. Conclusions: This qualitative study showed that patients' perspective differ according to the type of osteoporosis. A personalized assessment of patients' needs and objectives should then be performed before inclusion in educational programs. Patients have a major interest for non-pharmacological treatments and prefer group education. Disclosure of Interest: None Declared